Analisis Kelelahan Pekerja Over Time dan Shift pada Produksi Kerupuk Tahu dengan Metode Bourdone Wiersma - Fazrur Suman Prambahan; Boy Isma Putra (Universitas Teuku Umar, 2023)
UD Company. Dua Putra has a total of 5 employees and applies a working time system of 2 shifts per day. In the production process, the target that must be met within 1 month is 2000 packing crackers. From April 2022 to September 2022, the production output of tofu crackers experienced an average decrease of 17% or 350 packs of crackers. This is caused by changes in working hours and operator fatigue during production activities. In overcoming this problem, overtime is an option to complete the predetermined targets. The aim of this research is to measure the level of work fatigue and determine the factors causing fatigue among workers in tofu cracker production operators and provide suggestions for improvements to reduce the level of worker fatigue. The method used in this problem is the Bourdone Wirsma method, which is a simple measurement method that can determine mental work load and measure speed, accuracy and concentration as well as monotonous work in employees. From the analysis of the Bourdone Wirsma test method for speed levels, the results obtained were 80% of the weighted score results of